2022
DOI: 10.14740/jmc3934
|View full text |Cite
|
Sign up to set email alerts
|

Acute Interstitial Nephritis Induced by Clozapine

Abstract: Acute interstitial nephritis (AIN) classically presents as acute kidney injury most often induced by offending drugs. Less frequently it is secondary to infections, autoimmune disorders, or idiopathic conditions. Development of drug-related AIN is not dose dependent and a recurrence can occur with re-exposure to the drug. We present a 50-year-old male with treatment resistant schizoaffective disorder who developed clozapine-induced AIN, confirmed with kidney biopsy within 2 months of taking this medication. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…Together, these findings support the working model that innate immune activation, a hypothesized prerequisite to IDR progression, is unique to clozapine, while lymphopenia occurs via an independent mechanism that is conserved among analogues. Clozapine-altered chemistry parameters (e.g., ALT, BUN) may be relevant for other adverse effects including liver injury (Wu Chou et al, 2014;Oates et al, 2018;Gunther and Dopheide, 2023) and acute interstitial nephritis (Davis and Kelly, 2019;McLoughlin et al, 2022;Vantipalli et al, 2022), and these IDRs may share early mechanisms. Indeed, with repeat clozapine dosing, increased hepatic covalent binding (Gardner et al, 2005;Ip and Uetrecht, 2008) and inflammatory changes in the liver (Jia et al, 2014;Zlatkovic et al, 2014;Sernoskie et al, 2023) and the kidney (Mohammed et al, 2020) have been observed.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these findings support the working model that innate immune activation, a hypothesized prerequisite to IDR progression, is unique to clozapine, while lymphopenia occurs via an independent mechanism that is conserved among analogues. Clozapine-altered chemistry parameters (e.g., ALT, BUN) may be relevant for other adverse effects including liver injury (Wu Chou et al, 2014;Oates et al, 2018;Gunther and Dopheide, 2023) and acute interstitial nephritis (Davis and Kelly, 2019;McLoughlin et al, 2022;Vantipalli et al, 2022), and these IDRs may share early mechanisms. Indeed, with repeat clozapine dosing, increased hepatic covalent binding (Gardner et al, 2005;Ip and Uetrecht, 2008) and inflammatory changes in the liver (Jia et al, 2014;Zlatkovic et al, 2014;Sernoskie et al, 2023) and the kidney (Mohammed et al, 2020) have been observed.…”
Section: Discussionmentioning
confidence: 99%
“…The median age of the patients varies from 25 to 40 years of age [4,5]. The disease is more common in women as compared to men [3,6]. A few cases have also been reported in older individuals and in male patients [7].…”
Section: Discussionmentioning
confidence: 99%
“…Prednisone has also been studied as a mainstay of treatment with prednisone taper providing an adequate response in most of the patients [3]. In rare cases, the kidney function might not completely normalize [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, urinary retention and urinary incontinence are rare adverse effects [214], while sporadic cases of acute interstitial nephritis have been reported. Indeed, one of the most recent reports in the literature described the case of a 50-year-old schizoaffective man who developed acute interstitial nephritis induced by Clozapine, 300 mg daily, and recovered after the drug's interruption [215].…”
Section: Kidney Side Effectsmentioning
confidence: 99%